2020
DOI: 10.1007/s00063-020-00703-1
|View full text |Cite
|
Sign up to set email alerts
|

Prokalzitonin auf der Intensivstation

Abstract: Prokalzitonin auf der Intensivstation Differenzialdiagnose und Differenzialtherapie EinleitungErsetzen Biomarker das ärztliche Denken oder vermögen sie dieses zu bereichern?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…There have been some conflicting data about the utility of procalcitonin as a predictor of patient prognosis in clinical. [24,25] Some studies demonstrated a close association between evaluated procalcitonin and the severity of illness. Other studies also showed that the lack of a significant relationship between initial PCT level and patient outcomes is disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some conflicting data about the utility of procalcitonin as a predictor of patient prognosis in clinical. [24,25] Some studies demonstrated a close association between evaluated procalcitonin and the severity of illness. Other studies also showed that the lack of a significant relationship between initial PCT level and patient outcomes is disappointing.…”
Section: Discussionmentioning
confidence: 99%